Analysis The Effect Of Tax Avoidance, Leverage And Company Size On Income Smoothing Practices Of Manufacturing Companies Listed On The Indonesia Stock Exchange - Mubassyiriyah, Rizqiyatul; Sulestiyono, Deddy (DIPONEGORO UNIVERSITY, 2025)
This research aims to examine how Tax Avoidance, Leverage, and Company Size affect corporate income smoothing practices calculated using the Eckel Index formula. The population in this research uses a sample of companies in the basic materials manufacturing sub-sector listed on the Indonesia Stock Exchange for the 2022-2024 period. The sample was taken using purposive sampling, resulting in 40 research samples for the 3 years period from 2022 to 2024. This research data uses secondary data obtained from company financial reports through the Indonesia Stock Exchange website and the company's official website. In this research, the method used for hypothesis testing was logistic regression analysis using the SPSS program. Based on the statistical tests conducted in this research, it shows that tax avoidance has no effect on the company's income smoothing practices. Meanwhile, leverage and company size have a significant effect on the company's income smoothing practices.